The impact of Phytophthora ilicis on Ilex spp. in botanic garden collections: a case study at the Royal Botanic Garden Edinburgh - Elliot, Matt; Jones, Amanda (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2026)
Ilex spp. (holly) are widely planted ornamental evergreen shrubs which perform both an aesthetic and an ecological function in gardens. In Edinburgh, I. aquifolium is the second most common tree after Acer pseudoplatanus (sycamore), providing food and shelter for a range of species. Unfortunately, holly is under attack from a disease caused by the pathogen Phytophthora ilicis. This understudied pathogen has been in the UK for at least 35 years, but the impact has not been clearly elucidated. We undertook a study at the Royal Botanic Garden Edinburgh to understand the impact of this disease on Ilex spp. within a botanical plant collection. Our survey showed 14% of the collection was confirmed to be infected with P. ilicis, although true prevalence is probably underrepresented due to seasonal factors and detection challenges. We discuss possible management strategies for this disease.